Iodine-125 brachytherapy treatment for newly diagnosed brain metastasis in non-small cell lung cancer: A biocentric analysis - Yang, Lili; Wang, Congxiao; Zhang, Wei; Liu, Shifeng; Xuan, Tiantian; Jiang, Han; Hu, Xiaokun; Hu, Man; Li, Huanting (Frontiers in Oncology, 2022)
Purpose: The present study aimed to evaluate the safety and efficacy of the iodine-125 brachytherapy for newly diagnosed brain metastasis of non-small cell lung cancer (NSCLC). Materials and Methods-The study included 158 patients diagnosed with brain metastasis of NSCLC from December 2003 to August 2017. Ninety-nine patients underwent external beam radiotherapy (EBRT group), and 59 patients received iodine-125 brachytherapy (125I group). In addition, 6-month, 12-month progression-free survival (PFS) rate, 12-month, and 24-month overall survival (OS) rate were compared between the EBRT group and 125I group. Median OS and PFS were analyzed using the Kaplan-Meier method with a log-rank test. Results-The 6-month PFS rate was significantly higher in the 125I group (p=0.002), while no differences were found in the 12-month PFS rate (p=0.184). Also, the 12-month (p=0.839) and 24-month （p=0.284）overall survival (OS) rate had no statistical differences between the two groups. No significant differences were found between the two groups in median OS (p=0.525) and PFS (p=0.425). Conclusions-Iodine-125 brachytherapy offered an alternative therapy choice for patients who were not able to receive surgical resection besides EBRT.